Urothelial cancer: Once there were urologists, now oncologists joined, what about nephrologists?. Issue 1 (February 2018) - Cosmai, Laura; Launay-Vacher, Vincent; Porta, Camillo
Urothelial cancer is a family of neoplasms characterized by an extremely high incidence of kidney impairment throughout its whole natural history; furthermore, surgical and medical treatments may often worsen kidney function or cause renal adverse events. The role of the nephrologist would be key to support urologists and oncologists toward a really multidisciplinary management of these patients. First, nephrologists could help to deal with episodes of acute kidney injury, or of a worsening of chronic kidney disease due to obstruction/infections, episodes which are quite common in patients with non-muscle-invasive tumors undergoing several trans-uretral resections. In muscle-invasive neoplasms, the nephrologist could contribute to reduce the number of patients unsuitable for cisplatin-based neo-adjuvant (or adjuvant) chemotherapy or of those who cannot complete the scheduled treatment due to a deterioration in their kidney function. In patients receiving nephrectomy (in the case of upper urinary tract neoplasms) or cystectomy (in the case of bladder cancers), renal function deterioration is also extremely frequent; post-operative hydronephrosis, pyelonephritis, and uretero-enteric strictures indeed represent other potentially modifiable factors associated with a decrease in kidney function. Finally, in the metastatic setting, the nephrological management of renal toxicities from systemic therapies, including novel immune-checkpoint inhibitors, would also be increasingly important. Here, we highlight the need for the involvement of the nephrologist in the complex management of these patients, thus advocating for a really comprehensive multidisciplinarity.